2007
DOI: 10.1196/annals.1406.048
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL‐10 in Genetic Susceptibility to Coccidioidomycosis on Mice

Abstract: Epidemiological and clinical studies have confirmed that coccidioidomycosis is more severe in African American and Filipino patients than in Caucasians, suggesting a genetic basis for susceptibility in humans. We discovered that inbred strains of mice also vary greatly in their susceptibility to Coccidioides immitis infections, and although resistance is the dominant phenotype, it is a multigenic trait in mice. We found a strong direct correlation between susceptibility in mice and the amount of IL-10 made in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
4
7
0
Order By: Relevance
“…The amount of IL-10 transcript in the lungs of vaccinated mice showed no significant change between 8 and 12 DPC, while upregulation of IL-10 expression in lung homogenates of nonvaccinated mice revealed an approximate 35-fold increase during this same period postchallenge. These observations support previous findings indicating that there is a direct correlation between amounts of IL-10 production and susceptibility to Coccidioides infection (12,13).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The amount of IL-10 transcript in the lungs of vaccinated mice showed no significant change between 8 and 12 DPC, while upregulation of IL-10 expression in lung homogenates of nonvaccinated mice revealed an approximate 35-fold increase during this same period postchallenge. These observations support previous findings indicating that there is a direct correlation between amounts of IL-10 production and susceptibility to Coccidioides infection (12,13).…”
Section: Resultssupporting
confidence: 92%
“…(6), Cryptococcus neoformans (7), Histoplasma capsulatum (8), Pneumocystis carinii (9), and Aspergillus fumigatus (10). A correlation has been revealed between susceptibility to Coccidioides infection and the amount of IL-10 produced (11)(12)(13)(14). Loss of IL-10 production significantly improves the outcome of coccidioidomycosis in nonvaccinated mice (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that activation of the Th17 signal pathway is essential for protection against murine coccidioidomycosis (22,50,51) is further discussed below. The relatively low concentrations of IL-10 detected in the supernatants of immune splenocytes compared to IFN-␥ are consistent with the suggestion of a dynamic reciprocal relationship between these two cytokines (13). Dampened IL-10 production during early stages of coccidioidal disease may be a factor that contributes to the observed infiltration and expansion of activated CD4…”
Section: Discussionsupporting
confidence: 85%
“…14 We We, and others, have shown that susceptible and resistant mice show different immunological responses to experimental coccidioidomycosis. 2,27 While macrophages are important effector cells in the innate and acquired immune response to C. immitis, DCs are the most important antigen-presenting cells and different pathogens can modulate the way they affect the immune response. 28 Since Dectin-1 is also expressed on DCs, we compared the responses of DBA/2 and B6 bone marrowderived mDCs to FKS.…”
Section: Discussionmentioning
confidence: 99%